Pengaruh daya tarik wisata terhadap minat berkunjung di kawasan amahami kota bima - Sri Ernawati (Insight Management Journal, 2021)
The research objective was to determine and analyze the effect of tourism attraction on visiting interest in the Amahami area. The sample in this study amounted to 100 people with research instruments using a questionnaire with a Likert scale. Questionnaire data testing used validity and reliability tests. Data analysis used simple linear regression test and hypothesis testing using t test. The results of the study indicate that tourist attraction has a positive and significant effect on visiting interest in the Amahami area of Bima City